Intervención urbana integral de recuperación y transformación del espacio público de la ronda del caño Maizaro tramo central de la comuna 3 y 6 de la ciudad de Villavicencio (2021)
The integral urban intervention project for the recovery and transformation of the public space of the round pipe they caño Maizaro central section between the commune 3 and 5 of the city of Villavicencio, arises from an initial idea developed and worked on in research carried out at the Antonio Nariño University, where a reading of the state of the water courses that comprise our city was developed, specifically the caño Maizaro, since this pipe is of great importance and a clear environmental axis of the municipality.